Answer:
B
Explanation:
Simplify the numerator and denominator of the fraction, that is
-
Multiply the numerator/denominator of the first fraction by y
Multiply the numerator/denominator of the second fraction by x
-
=
Similarly
+
Multiply numerator/denominator of the first fraction by x
Multiply numerator/denominator of second fraction by y
+
=
To perform the division
leave the fraction on the numerator
Change division to multiplication
Turn the fraction on the denominator upside down, thus
×
Cancel xy on the numerator and denominator
=
← factor 2 out of each term on the numerator
=
→ B